Influence of the perforation configuration on dynamic behaviors of multilayered beam structure. (December 2020) - Almitani, Khalid H.; Abdelrahman, Alaa A.; Eltaher, Mohamed A.
Abstract: The novelty of this paper is to investigates the free vibration, frequency response and modal participation factors of the perforated multilayer microbeam structures using finite element analysis with different hole's geometry, filling ratio and array of hole. The three squared, rectangular, and circular configurations of perforation are considered through analysis. Elasto-dynamic finite element formulation is implemented. The natural frequencies for the three different perforation configurations at different number of holes are investigated. For better understanding of the dynamic behavior of multilayered perforated beam structure, both modal and harmonic responses are presented and discussed. To specify the most suitable vibrational mode for a certain degree of freedom for base excitation, both participation factor and the associated modal effective mass are presented and analyzed. The obtained results show the remarkable effect of perforation configuration and the number of holes throughout the cross-sectional area on the dynamic behavior of multilayered perforated beam structures. Different boundary conditions are considered through analysis. The obtained results are supportive for the design of perforated beam structures in both macro and micro-scales.